2010
DOI: 10.1002/uog.7730
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal reference ranges for umbilical vein blood flow at a free loop of the umbilical cord

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
63
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(74 citation statements)
references
References 68 publications
11
63
0
Order By: Relevance
“…25,44,45 Published data indicated that the largest umbilical vein diameter occurs during the third trimester, somewhere between 32 and 42 weeks GA. 50 The majority of published work over the last 17 years has modelled the relationship between the intra-abdominal or intra-amniotic umbilical vein velocity and GA as a positive linear trend, 12,[29][30][31]51 similar to that found in this research. 27,29,46 In this research, the diameter reached a peak value at 37 weeks GA and remained relatively stable until 40 weeks GA, before declining.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…25,44,45 Published data indicated that the largest umbilical vein diameter occurs during the third trimester, somewhere between 32 and 42 weeks GA. 50 The majority of published work over the last 17 years has modelled the relationship between the intra-abdominal or intra-amniotic umbilical vein velocity and GA as a positive linear trend, 12,[29][30][31]51 similar to that found in this research. 27,29,46 In this research, the diameter reached a peak value at 37 weeks GA and remained relatively stable until 40 weeks GA, before declining.…”
Section: Discussionsupporting
confidence: 73%
“…43,44 The ICC is considered superior to Pearson's and Spearman's analyses as it takes into account the differences between observers 42 and the variance of all measurements. 27,29,46 In this research, the diameter reached a peak value at 37 weeks GA and remained relatively stable until 40 weeks GA, before declining. 25,44,45 Published data indicated that the largest umbilical vein diameter occurs during the third trimester, somewhere between 32 and 42 weeks GA.…”
Section: Discussionsupporting
confidence: 47%
See 2 more Smart Citations
“…The oxygenated nutrient‐rich blood returns to the fetus via a single umbilical vein (UV). The UV is a thin‐walled blood vessel, which has a sonographically measured average diameter of approximately 1.0–2.5 mm during 11–18 weeks and 2.5–6.7 mm in the intra‐abdominal portion and 3.5–8.0 mm in the free loop of the umbilical cord at 18–41 weeks of gestation. The mean diameter of UV measured within 5‐s after delivery in the umbilical cord is reported to be approximately 6.6 mm at term .…”
Section: Feto‐placental Circulationmentioning
confidence: 99%